Oskarżeni o separatyzm. Działania tajnych służb PRL wobec działaczy kaszubskich w latach 1945–1970 - Paczoska, Alicja (Pamięć i Sprawiedliwość, 2004)
Accusing Kaszuby inhabitants of separatism was not the idea of communist security service. In the interwar period the „sanacja” authorities suspiciously treated activities of some of the representatives of Kaszuby movement. When after the end of WW II in the autumn of 1945 Kaszuby movement became active again and began making efforts to edit a magazine in Kaszubian, Security Service became interested in it.Into the circle of „zrzeszeńcy” (people connected with a paper „Zrzësz Kaszëbskô”) secret agents were introduced. They reported the initiatives of each of the activists. Representativesof Kaszuby movement were being observed (cases such as „Działacze” – „Activists”, „Odrębność – „Separation”, „Ratusz” – „City Hall”), it was to provide evidence for their anti-state activity. Their private correspondence was read, their telephones and rooms were listened to, special „preventive” talks were led with them to intimidate them. Among those under special surveillance were Jan Trepczyk, Jan Rompski, Aleksander Labuda and Ignacy Szutenberg.Starting with 1956 the Security Service was weakening the activity of Kaszuby Association, which, according to the Service, gathered opponents of Communist regime. It was tried to set its members at variance, to isolate and disgrace the most active of them. Secretagents were reporting on meetings of Main Board and in local branch offices, so the Security Service was well informed about personal conflicts within the Association and used that knowledge to weaken its activity.The repressions of Security Service against Kaszubian intellectuals gathered in Kaszuby movement have by no means limited their activity. It was not possible to publish some of important papers on Kaszuby inhabitants or in Kaszubian. However, actions of the security service did not prove Kaszubian aspirations to found their own republic or to collaborate with the Germans. That accuse was so groundless that no representative of Kaszuby movement was prosecuted by the Communist administration of Justice.